Conducting Mode 2 research in HRM: A phase‐based framework. Issue 1 (28th May 2018) - Guerci, Marco; Radaelli, Giovanni; Shani, Abraham B. (Rami)
Abstract : Recent studies in the field of human resource management (HRM) have highlighted that current research is mostly performed and consumed by academics, and is driven by theoretical and disciplinary concerns rather than practical ones. This debate has invoked the need to produce more Mode 2 research in the HRM field, that is, research driven by practical problems that integrate collaborative efforts by academics and practitioners. Yet, guidelines on how academics and practitioners may implement Mode 2 research remain disjointed and incomplete. Our study provides a phase‐based collaborative‐based framework for the implementation of Mode 2 research in the HRM field, in ways that both academic rigor and practical relevance are achieved. Our framework is informed by a comprehensive review of previous Mode 2 research, within and outside the HRM field. The proposed framework details four macro‐phases: the codevelopment of research questions with practitioners; the design of collaborative spaces and mechanisms; the design and management of double‐loop iterative research processes; and finally the academic and practice legitimization of Mode 2 outcomes. Our framework has the objective to support HRM researchers and practitioners, as well as relevant institutions and gatekeepers in the design, implementation, education, and assessment of Mode 2 research.